(untitled) (Research, Society and Development, 2023)
Objective: to investigate in the literature the effects of the association of dexamethasone and dexmedetomidine adjuvants in peripheral nerve blocks with local anesthetics. Method: This is a systematic literature review, through the search in the databases, namely: Medical Literature Analysis and Retrieval System online (MEDLINE/PubMed), Latin American Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO). Data collection took place from September to November 2022. The inclusion criteria were: randomized, retrospective, prospective, cross-sectional and case report studies, without distinction of gender or race, which used dexamethasone or dexmedetomidine or both for blockade of the peripheral nerves and published in the last 10 years (2012-2022). Regarding the exclusion criteria were: the use of other substances that are not characterized as anesthetics or vasoconstrictors; memorials, editorial letters, reviews, research with individuals who had comorbidities, such as peripheral vascular disease, allergy to local anesthetics, pregnant women, history of cardiovascular or liver disease, and studies with more than 10 years of publication. Results: 532 relevant studies were identified from the searched databases, of which 329 were excluded after checking the titles, and 203 of the remaining articles were analyzed based on the title and its compatibility with the inclusion and exclusion criteria. These had their abstracts read, 09 of which were selected for full-text evaluation for eligibility and subsequently included in the qualitative analysis. Conclusion: The review demonstrated that dexamethasone and dexmedetomidine are good adjuvants when used in peripheral nerve blocks, increasing the duration of analgesia, but with some differences in effects.